La guerra sin fin - Amias, Jennie; Marrs, Audrey; Vogelson, Jessie; Ferguson, Charles, 1955-; Scott, Campbell; Armitage, Richard; Wilkerson, Lawrence B. ([New York, N.Y.] : Magnolia Home Entertainment, 2007)
Observaciones de personas del gobierno de Estados Unidos sobre la invasión a Irak en el 2003 y la subsecuente ocupación, comentarios extras de oficiales de altos rangos, civiles iraquíes, soldados estadounidenses y analistas prominentes. Examina la política de la administración de George W. Bush y las decisiones tomadas en el marco de la invasión y sus consecuencias en Irak, incluyendo temáticas como las bajas de las tropas estadounidenses, insuficientes niveles de tropas desplegadas en el país, el descontrolado saqueo a Bagdad, la purga de profesionales del gobierno Iraquí, lo disolución de los militares nacionales de Iraquíes y la subsecuente oleada de caos político y civil.
En inglés con subtítulos opcionales en español; closed-captioned.
Narrator: Campbell Scott ; interviews with: Deputy Secretary of State Richard Armitage, Colonel Lawrence Wilkerson, Larry Diamond, General Jay Garner.
Director of photography, Antonio Rossi ; editors, Chad Beck, Cindy Lee ; original music, Peter Nashel.
DVD, region 1; Dolby Digital 5.1 surround, Dolby Digital 2.0 stereo.
Not rated.
Special features: extended interview with Richard Armitage (12 min.); extended interview with Iraq human rights deputy minister Aida Ussayran (8 min.); extended interview with Washington Post Baghdad bureau office manager Omar Fekeiki (8 min); "Personal Story: Larry Diamond" (3 min.); "Life under Saddam" interview with Iraqi Ambassador Faisal Al-Istrabadi (2 min.); "De-Baathification" interview with General Jay Garner (3 min.); "Disbanding the Iraqi Army" video letter produced for the New York Times web site (11 min.); "The CPA" further insider insights on the alition Provisional Authority (7 min.); "Kidnapping and crime" regarding the civil disarray during the occupation (2 min.); "U.S. military conduct" (5 min.); "Could it have been different?" (2 min.); "Was it worth it?" (3 min.); "Consequences" (6 min.); "Footage of Iraq" slice-of-life scenes of Iraq during the occupation (10 min.).
Keywords: Estados Unidos -- Historia militar -- Siglo XXI; Irak -- Historia -- 2003-; Cine documental; Películas cinematográficas